Evaluation of the Implementation of the Posyandu Program Elderly in Aceh Utara - Ernawati, Ernawati; Ti Aisyah, Ti Aisyah; Aiyub, Aiyub; Ferizaldi, Ferizaldi (Malikussaleh Social and Political Reviews, 2024)
The Elderly Posyandu Program is a manifestation of the government's concern in dealing with adequate health and welfare problems for the elderly. This program is intended so that the elderly who are vulnerable to diseases can live healthy, independent and useful lives so that they do not become a burden to their families and the surrounding community. This study aims to evaluate the Posyandu Elderly Program including the factors that inhibit its implementation, the method in the research uses a qualitative research model is descriptive. The results of the research on health examination activities showed that the examinations carried out included: measurement of body mass index consisting of weight and height measurements, blood pressure checks, blood sugar and cholesterol level checks, counseling and health counseling activities. For additional feeding activities, it is carried out to meet the nutritional adequacy of the elderly in the form of rice, bread, fruit and milk. The inhibiting factor is motivated by the lack of public knowledge and understanding regarding the importance of elderly posyandu for the elderly. In addition, another inhibiting factor is the lack of facilities and infrastructure to support the elderly posyandu program, such as health facilities, examination tools, and educational programs. Based on the results of this research, it is relevant that the data of this program is continued by increasing public understanding through socialization, changing and maximizing facilities and infrastructure for the better.